The Analysis of “Anak Pintar Seri English? No Problem!” For English Language Learning - Rika Hendryani (Institute of Research and Community Outreach - Petra Christian University, 2017)
The present study is aimed to find out the extent to which Anak Pintar seri English? No Problem! meet the 10 principles for designing video games for foreign learning proposed by Purushotma, Thorne, and Wheatley (2009). This study is a qualitative research that took the writers approximately 5 hours to play. The findings of this study show that Anak Pintar seri English? No Problem! matches 5 principles, for example, the principles of “content organized around tasks” and “metalinguistic descriptions and terminology presented as a supporting material”. The result of this study hopefully would be beneficial to the studies of video games for foreign language learning and for those that wish to evaluate or use video games as a learning tool.